Nurses’ perception of the impact of professional development sessions on their pre-hospital clinical practice with trauma victims - Mota, Mauro; Pires, Regina; Cunha, Madalena; Santos, Margarida Reis (Frontiers in Public Health, 2024)
Background Continuing education is important for the quality of clinical practice because it complements it and focuses primarily on producing qualified pre-hospital nurses with operationally defined competence in nursing standards. The objective of this study was to assess pre-hospital nurses’ opinion of the impact of professional development sessions on their clinical practice. Method A descriptive and quantitative study was carried out involving Portuguese pre-hospital nurses. Six professional development sessions were presented in 2020 to pre-hospital registered nurses in four of Portugal’s main cities. To collect the data, at the end of each session, we apply a questionnaire designed specifically for this study. This data collection instrument consists of 11 questions, six designed to evaluate the session and five designed to evaluate the trainer responsible for the session. A five-point Likert scale was used for each question, where 1 corresponds to very dissatisfied and 5 to extremely satisfied. Results Two hundred and two nurses, which represents 55% of all Portuguese pre-hospital nurses, took part in the assessment of the professional development sessions. The nurses were from the Northern region of Portugal (51%; n = 102), the Centre region (29%; n = 59) and the Southern region of Portugal (20%; n = 41). Nurses found the session extremely satisfactory. All the assessment scores ranged between 4.4 and 4.7 points, on a scale of 1 to 5. 76.2% of the participants considered that the knowledge acquired could have a major impact [score = 5] on their future clinical practice. The majority of pre-hospital nurses (96.5%) felt that the session could have a major impact [score = 5; 76.2%, n = 154] or a very important impact [score = 4; 20.3%, n = 41] on their clinical practice. Conclusion The professional development sessions provide pre-hospital nurses with the latest research findings and the majority of nurses considered that the training had a huge impact on their clinical practice. However, it is important that future research aims to explore the cause-effect relationship between training and improved clinical practice.